Design and fabrication of an electrochemical chip for liquid-phase transmission electron microscopy. (4th May 2022) - Sasaki, Yuki; Mizushima, Ayako; Mita, Yoshio; Yoshida, Kaname; Kuwabara, Akihide; Ikuhara, Yuichi
Abstract: Liquid-phase transmission electron microscopy (LP-TEM) can be used with an electrochemical chip (e-chip) to observe electrochemical reactions in a liquid in situ . The design of electrodes on an e-chip fabricated using microelectromechanical system technology cannot be easily changed. Here, we report a newly designed e-chip and its fabrication process. Electrodes with a desired shape were fabricated with various metals via an additional step of vacuum deposition onto our e-chip with a shadow mask. For precise control of the electrochemical reactions in LP-TEM, optimization of the electrode shape and material is critical.